Synthesis and optimization of methyl 5-acetyl-1,4-dihydro-2,6-dimethyl-4-(substituent benzylidene)pyridine-3-carboxylate - Liu, Rui Dong; Zhang, Jian (European Journal of Chemistry, 2011)
Two 1,4-dihydro-Hantzsch pyridine derivatives were synthesized by three steps. In the condensation step, the reaction time can be shortened to 1.5 h through using H2SO4-acetic anhydride system as a catalyst rather than the acetic acid-piperidine systemin the cyclization step, the reaction time was shortened from 20 h in ethanol to 15 h in polar aprotic solvent, and the yield of two products also was increased from 43.3% and 39.7% in traditional solvent to 93.2% and 90.1% in polar aprotic solvent.